XRCC1 prevents toxic PARP1 trapping during DNA base excision repair - Demin, Annie A; Hirota, Kouji; Tsuda, Masataka; Adamowicz, Marek; Hailstone, Richard; Brazina, Jan; Gittens, William; Kalasova, Ilona; Shao, Zhengping; Zha, Shan; Sasanuma, Hiroyuki; Hanzlikova, Hana; et al. (Molecular cell, 2021)
Mammalian DNA base excision repair (BER) is accelerated by poly(ADP-ribose) polymerases (PARPs) and the scaffold protein XRCC1. PARPs are sensors that detect single-strand break intermediates, but the critical role of XRCC1 during BER is unknown. Here, we show that protein complexes containing DNA polymerase β and DNA ligase III that are assembled by XRCC1 prevent excessive engagement and activity of PARP1 during BER. As a result, PARP1 becomes "trapped" on BER intermediates in XRCC1-deficient cells in a manner similar to that induced by PARP inhibitors, including in patient fibroblasts from XRCC1-mutated disease. This excessive PARP1 engagement and trapping renders BER intermediates inaccessible to enzymes such as DNA polymerase β and impedes their repair. Consequently, PARP1 deletion rescues BER and resistance to base damage in XRCC1-/- cells. These data reveal excessive PARP1 engagement during BER as a threat to genome integrity and identify XRCC1 as an "anti-trapper" that prevents toxic PARP1 activity.
Keywords: DNA vazebné proteiny; oprava DNA; Animals; DNA Damage; Poly(ADP-ribose) Polymerases; buněčné linie; DNA-polymerasa beta; DNA Polymerase beta; Fibroblasts; vazba proteinů; DNA; DNA-ligasa ATP; lidé; poly(ADP-ribosa)polymerasa 1; PARP inhibitory; DNA Repair; fibroblasty; Cell Line; Poly (ADP-Ribose) Polymerase-1; poškození DNA; DNA-Binding Proteins; poly(ADP-ribosa)polymerasy; X-ray Repair Cross Complementing Protein 1; jednořetězcové zlomy DNA; zvířata; Poly(ADP-ribose) Polymerase Inhibitors; protein XRCC1; Protein Binding; DNA Ligase ATP; DNA Breaks, Single-Stranded; Humans